(untitled) (Journal of the Bangladesh Agricultural University, 2012)
The present study was conducted over 4 months during 1st September to 30th December 2005 to observe the effects of stocking density on growth and survival of Thai Sharpunti, Barbodes gonionotus in 3 earthen ponds of size of 2.8 decimal each. The stocking densities of 80, 100 and 120 fish/decimal were treated as T1, T2 and T3, respectively. All the treatments were subjected to the same feeding regime and fertilization. The range of water quality parameters such as temperature were 30.31, 30.16 and 29.65 0C, transparency were 29.94, 37.63, and 40.02 cm, water depth were 143.91, 148.67 and 151.54 cm, dissolved oxygen were 4.72, 4.35 and 4.24 mg/l, pH were 7.71, 7.49 and 7.31, plankton biomass were 43.05 x 105 /l, 37.97 x 105 /l and 36.05 x 105 /l in T1, T2 and T3, respectively. Among the growth parameters, mean weight gain were 48.87 g, 41.43 g and 34.09 g, percent weight gain were 698.21%, 591.93% and 487%, the average daily gains were 1.65, 1.54 and 1.20 g, the specific growth rate were 1.73, 1.61 and 1.47%, in T1, T2 and T3 respectively. The gross total productions of Barbonymus gonionotus were 1041.96, 1085.71 and 1019.64 kg/ha/120 days while the net productions were 911.60, 929.46 and 846.43 kg/ha/120 days in T1, T2 and T3, respectively. The gross and net total productions in T2 were highest among the treatments. The highest growth and survival rate were obtained in T1. DOI: http://dx.doi.org/10.3329/jbau.v9i2.11048 J. Bangladesh Agril. Univ. 9(2): 327338, 2011